The Rule of Law and the Public Transcript: The Accompong Maroons and the Colonial Jamaican Government's Dispute about Fullerswood Estate. - Thompson, Michelle Dionne (Caribbean Quarterly, 2020)
The article discusses issues on the rule of law and public transcript in the dispute between the Accompong Maroons and the colonial Jamaican government over the Fullerswood Estate in 1894-1899. Also cited are the efforts by the Maroons led by Major Robert Stone to develop the property, the negotiations to resolve the dispute, and the use of the 1842 Land Allotment Act as the basis of judgment.